Semisynthetic nanoreactor for reversible single-molecule covalent chemistry. - Lee, J; Boersma, A; Boudreau, M; Cheley, S; Daltrop, O; Li, J; Tamagaki, H; Bayley, J (American Chemical Society, 2016)
Protein engineering has been used to remodel pores for applications in biotechnology. For example, the heptameric α-hemolysin pore (αHL) has been engineered to form a nanoreactor to study covalent chemistry at the single-molecule level. Previous work has been confined largely to the chemistry of cysteine side chains or, in one instance, to an irreversible reaction of an unnatural amino acid side chain bearing a terminal alkyne. Here, we present four different αHL pores obtained by coupling either two or three fragments by native chemical ligation (NCL). The synthetic αHL monomers were folded and incorporated into heptameric pores. The functionality of the pores was validated by hemolysis assays and by single-channel current recording. By using NCL to introduce a ketone amino acid, the nanoreactor approach was extended to an investigation of reversible covalent chemistry on an unnatural side chain at the single-molecule level.